Relationship of early participation in physical activities to persistent post-concussive symptoms following acute paediatricpediatric concussion. Issue 11 (25th May 2017) - Zemek, Roger; Grool, Anne M; Aglipay, Mary; Momoli, Franco; Meehan, William P; Freedman, Stephen B; Yeates, Keith Owen; Gravel, Jocelyn; Gagnon, Isabelle; Boutis, Kathy; Meeuwisse, Willem; Barrowman, Nick; et al.
Abstract : Trial Registration: Clinicaltrials.gov Indentifier: NCT01873287 . Objective: To investigate if early physical activity (7-days post-injury) was associated with lower risk of persistent post-concussive symptoms (PPCS) compared to guideline-recommended conservative rest. Design: Prospective, multicenter, cohort study. Setting: Nine tertiary Canadian Paediatric EDs. Participants: 2413 children (61% male) aged 5-18 years with acute concussion (<48 hours) with inclusion/exclusion criteria per Predicting Persistent Post-concussive Problems in Paediatrics (5P) study. Assessment of risk factors: Participation in physical activities, post-concussive symptoms, and concussion modifiers were assessed using standardised questionnaires at baseline, 7- and 28-days post-injury. Outcome measures: PPCS (primary outcome) was defined as ≥3 new or worsening symptoms on Post-Concussion Symptom Inventory at 28-days post-enrolment. The relationship between early physical activity and PPCS was examined using regression, 1:1 propensity-matched, and inverse probability of treatment weighting (IPTW) analyses. Results: PPCS occurred in 678/2413 (30.1%) participants. Most children (n=1677, 70%) participated in physical activity at one-week of which only n=528 (31%) were symptom-free. Early physical activity was associated with reduced likelihood of PPCS [regression: OR=0.42, (95% CI: 0.35–0.51)]. Early activity remained associated with reduced PPCS risk when matched 1:1 for propensity score [n=1290, OR=0.56, (95% CI: 0.44–0.71)], and using IPTW [n=2235, OR=0.62, (95% CI: 0.51–0.76)]. Sensitivity analyses (replacement of baseline symptoms with one-week symptoms) maintained significant associations [regression: OR=0.42, (95% CI: 0.35–0.51); propensity matching: OR=0.75, (95% CI: 0.60–0.94); and IPTW: OR=0.69, (95% CI: 0.57–0.85)]. Conclusions: Physical activity within 7-days post-injury was associated with lower risk for PPCS in youth recovering from acute concussion. RCTs are urgently needed to confirm these findings and to determine the optimal timing of the initiation of physical activity. Competing interests: No competing interests to disclose. This study was supported by Canadian Institutes of Health Research (CIHR) Operating Grant MOP:#126197; CIHR-Ontario Neurotrauma Foundation Mild Traumatic Brain Injury Team Grant TM1:#127047; and CIHR planning grant MRP: #119829. None.